Estimating costs of bedside assessment by a judge in each case of mechanical restraint in Germany after new legislation - Hirsch, Sophie; Flammer, Erich; Steinert, Tilman (Frontiers in Psychiatry, 2024)
Background In 2018, the German Federal Constitutional Court decided that mechanical restraint is the most intrusive coercive measure and its use requires a judge’s decision after bedside assessment if lasting longer than 30 min. Subsequently, legal changes were realized. The objective of our study was to determine the number of saved coercive episodes and saved hours in seclusion or restraint in 2019 compared to the average of the previous years, 2015–2017, as well as costs per saved episode, hour, and case saved from any coercive measure. Methods We used data from the Baden–Wuerttemberg case registry for coercive measures, covering all 32 psychiatric hospitals of the Federal State and 435,767 admissions in the study period. Time expenditure was calculated as 3.5 h with an average of 51.95 € per working hour on the side of the justice system and 1.5 h (45.94 €/h) on the side of the hospital per case. Results The number of coercive episodes decreased by 10.0% from 28,181 (average 2015–2017) to 25,371 (2019). The number of hours in seclusion or restraint decreased by 17.9% from 321,956 (2015–2017) to 264,423 (2019). This resulted in the cost of 872.33 € per saved episode and 42.61 € per saved hour in seclusion or restraint. Conclusion Given the correctness of our estimations, saving 1 h in coercion by less than 1 h of an expert’s work might be justified from an ethical and economic perspective.